Assessing the adolescent experience of mindfulness - Lechtenberg, Marcie M. (Kansas State University, 2012)
This investigation explored a relatively understudied aspect of mindfulness: the experience of ninth graders in a public school classroom who practice a brief, daily mindfulness activity. The mixed-method study utilized both qualitative and quantitative research methods. Semi-structured interviews investigated the experience of those students and gleaned further information surrounding the question, ―What was the experience of mindfulness like for you?‖ The data from these interviews was analyzed using thematic analysis and was cross-coded by two outside researchers not part of the data collection. This study also explored the effects of classroom mindfulness activities through the Child and Adolescent Mindfulness Measure (Greco, Dew, & Baer, 2005). The participating students and a control group of students within the same school building and subject area took the measure before and after the study to determine the effects, if any, of participating in classroom mindfulness activities on adolescent mindfulness. These results were analyzed using paired sample T-tests using SPSS software. Results from both the interviews and the survey showed that students participating in the mindfulness activities had a consistently positive experience with the mindfulness exercise and increased their level of mindfulness. While unfamiliar with mindfulness at the beginning of the study, students in the experimental condition reported they found the experience beneficial in terms of personal growth, classroom environment, and adaption to other areas of their life. Any negative experiences concerning the mindfulness exercises centered around the initial unfamiliarity with mindfulness and specific components of one exercise. These results were further confirmed by the entries in a daily journal kept by the teacher.
Keywords: Mindfulness; Adolescents; Relational frame theory; Child and adolescent mindfulness measure; Behavioral Sciences (0602); Education, General (0515)